(untitled) (Global Journal of Medical Research, 2020)
Coronavirus disease 2019 (COVID-19) has become an important cause critical care admission worldwide. In the context of newly described multisystem inflammatory syndrome temporally related to SARS-CoV-2 (PIM-TS), the question of liver compromise came into evidence. Our group summarized a case series of 6 critically ill COVID-19 pediatric patients that presented some degree of liver damage, as demonstrated by liver and/or canalicular enzymes elevation, a yet not fully explored characteristic of the infection in the pediatric patient, that may indicate a more severe progression. Observations regarding the role of systemic inflammatory response can be taken from the described cases.